Faculty Assessment Fellows: Shifting from a Culture of Compliance to a Culture of Assessment Advocacy. Issue 177 (9th October 2018) - Hong, Rebecca
Abstract: This chapter examines the current pressures and realities in higher education assessment and highlights one campus' effort toward equipping faculty to move toward a learner‐centered approach in teaching, learning, and assessment. It proposes a model of faculty development that integrates best practices of professional development with cultivating faculty self reflexivity as practitioner and advocate for equity in student learning. The chapter ends with lessons learned in preparing faculty as assessment fellows and recommendations for campuses seeking to engage their faculty in a similar opportunity.